2012
DOI: 10.2471/blt.11.092494
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary polio immunization activities and prior use of routine immunization services in non-polio-endemic sub-Saharan Africa

Abstract: Large percentages of children participated in SIAs. Prior use of routine immunization services and compliance with the routine OPV schedule showed a strong positive association with SIA participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Other authors [ 4 , 7 , 17 ] reached similar conclusions using NP-AFP and NICS 2006 data to estimate coverage with type 2-containing OPV. Moreover, asides the drop in the RI in the affected LGA, the environmental characteristics of the case-patient may also contribute towards the emergence of the infection.…”
Section: Outbreak Investigation Reportsupporting
confidence: 59%
“…Other authors [ 4 , 7 , 17 ] reached similar conclusions using NP-AFP and NICS 2006 data to estimate coverage with type 2-containing OPV. Moreover, asides the drop in the RI in the affected LGA, the environmental characteristics of the case-patient may also contribute towards the emergence of the infection.…”
Section: Outbreak Investigation Reportsupporting
confidence: 59%
“…This finding was also consistent with the previous study which found very low SIA coverage among non-users of routine immunization services. This study further recommended that SIA monitoring in the GPEI should include an assessment of the vaccination history of children "missed" by vaccination teams during SIAs [29]. Our study also pointed out that the sweeping method which was being used in the areas of highly security compromised situations was prone to miss houses and children as micro-planning was less likely to be used in the approach.…”
Section: Experts' Recommendationmentioning
confidence: 70%
“…Quantification of these factors would serve to improve the association between vaccine coverage and incidence across countries. Also, as previously demonstrated 56 , an assessment of the vaccination history of children not vaccinated during SIAs would help identify the possible pockets of susceptible individuals. In addition, accounting for the geographic variation in quality of conducted SIAs could help describe the heterogeneity in incidence data.…”
Section: Discussionmentioning
confidence: 85%